Inhibition of lncRNA DILC attenuates neuropathic pain via the SOCS3/JAK2/STAT3 pathway. Issue 6 (17th June 2020) - Liu, Yujie; Feng, Lu; Ren, Shichao; Zhang, Yingxiu; Xue, Jing
Abstract: Long noncoding RNAs (lncRNAs) have been involved in the development of multiple pathological processes including neuropathic pain. The aim of the present study is to investigate the role of lncRNA down-regulated in liver cancer stem cells (DILC) in the progression of neuropathic pain and its underlying mechanism. Neuropathic pain rat model was established with the bilateral chronic constriction injury (bCCI) method. The results from quantitative PCR analysis in the spinal cord showed that DILC was significantly up-regulated in rats with bCCI compared with the sham group. DILC down-regulation mediated by intrathecal administration of DILC siRNA significantly increased the mechanical shrinkage threshold (MWT) and paw withdrawal threshold latency (PWTL), decreased the positive frequency for nerve sensitivity to cold and suppressed the expression of inflammatory genes in bCCI rats. Down-regulation of DILC induced suppressor of cytokine signaling (SOCS3) expression and inhibited the phosphorylation of signal transducer and activator of transcription 3 (p-STAT3) in spinal cord tissues. Western blotting showed that down-regulation of DILC by DILC siRNA transfection induced SOCS3 expression and inhibited the expression of p-Janus kinase 2 (p-JAK2) and p-STAT3 and their downstream genes in primary microglia . Furthermore, down-regulation of DILC increased the viability of primary microglia, suppressed apoptosis, and inhibited the production of interleukin (IL)-6 and IL-1β in microglia. In contrast, overexpression of DILC showed the opposite functions to those of DILC knockdown. In conclusion, silence of lncRNA DILC attenuates neuropathic pain via SOCS3-induced suppression of the JAK2/STAT3 pathway.